2009
DOI: 10.1177/0042098009339427
|View full text |Cite
|
Sign up to set email alerts
|

The Gap between Free Market and Social Optimum in the Location Decision of Economic Activity

Abstract: This article presents a simplified model for comparison of the spatial distribution (core—periphery) of economic activity resulting from free market conditions, with the distribution that would lead to a social optimum. It further examines the public policy measures required to lead the economy towards the optimal distribution. Simulations are conducted to illustrate the mechanism of intervention of public policy and to test the feasibility of various measures. An important conclusion is that public investment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
7
0
3
Order By: Relevance
“…For investigation purposes, 290 Swedish municipalities are merged into 90 local labor markets (LLMs) that are defined by statistics of commuting in the way that maximizes self-containment of commuting flows within a region (Statistics Sweden 2010). Non-core regions are defined as those beyond the metropolitan areas and their surroundings (Lagendijk and Lorentzen 2007;Malul and Bar-El 2009). In case of Sweden, the LLMs of three largest cities-Stockholm, Gothenburg, and Malmö-are considered as metropolitan regions, while the remaining 87 LLMs are classified as non-core regions.…”
Section: Data and Definitionsmentioning
confidence: 99%
“…For investigation purposes, 290 Swedish municipalities are merged into 90 local labor markets (LLMs) that are defined by statistics of commuting in the way that maximizes self-containment of commuting flows within a region (Statistics Sweden 2010). Non-core regions are defined as those beyond the metropolitan areas and their surroundings (Lagendijk and Lorentzen 2007;Malul and Bar-El 2009). In case of Sweden, the LLMs of three largest cities-Stockholm, Gothenburg, and Malmö-are considered as metropolitan regions, while the remaining 87 LLMs are classified as non-core regions.…”
Section: Data and Definitionsmentioning
confidence: 99%
“…Pravzaprav se trženje regij in mest kot orodje politike pogosto uporablja za sprejemanje podobe regije (Paddison, 1993) in s tem za spodbujanje regionalnega gospodarstva s pritegnitvijo novih naložb (Kearns in Philo, 1993;Short idr., 1993). Najprej smo razvili poenostavljen model, ki kaže uravnoteženo prostorsko porazdelitev podjetij med središčem in obrobjem, nato pa smo ga razširili tako, da smo v analizo vključili dejavnik dojemanja (kar temelji na modelu, ki sta ga razvila Miki Malul in Raphael Bar-El; glej Malul in Bar-El, 2009a, 2009b. Opisu teoretičnega modela sledi empirična analiza dejavnikov dojemanja na podlagi opravljene ankete.…”
Section: Uvodunclassified
“…Naša analiza temelji na modelu, ki sta ga razvila Malul in Bar-El (2009a, 2009b, pri čemer bomo najprej opisali glavna načela delovanja tega modela, ki mu bomo nato dodali še učinek dojemanja. Zaradi poenostavitve predvidevamo, da sta v preučevanem gospodarstvu samo dve regiji.…”
Section: Osnovni Modelunclassified
See 1 more Smart Citation
“…Examining 140 schools in Ohio, Haurin and Brasington (1996) showed that a 1% increase in the achievement of the ninth grade increased house prices by an average of 0.5%, with housing prices being a proxy for the level of satisfaction of the residents. Education also emerged as a significant factor for companies when choosing where to locate (George, 1882;Malul and Bar-El, 2009).…”
Section: Introductionmentioning
confidence: 99%